Reactions of 1-Amino-5-Benzoyl-4-Phenyl-1H-Pyrimidine-2-Thione with Various Carboxylic Anhydrides - Onal, Zulbiye; Altural, Behzat (Asian Journal of Chemistry, 2010)
1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-thione (1) reacts with various carboxylic anhydrides (2a–e) under different conditions and gives the new amide and imide derivatives. Reaction of (1) with maleic anhydride (2b) resulted in acid derivative (3b). The structures of these compounds (3a–f) were determined by 1H NMR, 13C NMR, IR spectra and elemental analysis.